THE EFFECT OF SMALL AND MEDIUM BUSINESS UPON THE ECONOMIC POTENTIAL OF A REGION - A. A. Alkhazov (Финансы: теория и практика, 2017)
The paper is concerned with the development of a methodology to assess the impact of small and medium-sized businesses on the economic potential of a region. The state and the development trends of the small and medium business sector in the country are examined. A number of methodological approaches to the assessment of the economic potential are described. The entire economic potential is broken down into individual components laying the emphasis on the role of small and medium-sized businesses in their formation. In the development of the methodology for assessing the effect of small and medium-sized businesses on the economic potential of a region it is recommended to identify the basic structural elements of the economic potential that are directly affected by the sector. The above elements can be interpreted through five aggregate indices each of which includes a number of specific indicators characterizing the development of the small and medium-sized business sector in the region. The proposed methodology helps identify the most effective forms and types of the small and medium-sized entrepreneurship in individual areas of the economy, which makes it possible to pinpoint development centers represented by successful entities and through their support increase the efficiency of the entire segment of small and medium-sized businesses.